Pengelolaan bank sampah melalui Simbah (Sistem Informasi Bank Sampah) guna meningkatkan akuntabilitas dan transparansi - Pratiwi, Desy Nur; Pravasanti, Yuwita Ariessa; Dewi, Maya Widyana; Asadduluh, Asadduluh; Gustiani, Ike (Nur Science Institute, 2025)
The purpose of this community service activity is to improve the accountability and transparency of the Pagar Idum waste bank. This increase in accountability and transparency is through the Simbah application (waste bank information system). The method for implementing this community service activity starts with surveys and interviews on partner problems, socialization of accountability and transparency, and training on the use of the Simbah application. The participants in this activity were 60 active members of the waste bank. The results of this activity showed that partners experienced a 40% increase in understanding of accountability and transparency (before the activity, 45%; after the activity, 85%). Based on observations during the training on the Simbah application, 80% of partners were able to use it, although some participants still experienced difficulties.